Disaster management : preparedness and mitigation - Akbar, Saima; Singh, Suraj Kumar, 1983-; Kanga, Shruti, 1984- (ISTE Ltd ; John Wiley & Sons, Inc., 2024)
Disaster Management embarks on a comprehensive exploration of proactive approaches to confronting the ever-growing challenges posed by natural and man-made disasters. Drawing on a wealth of interdisciplinary research and practical expertise, this book delves into the core principles of disaster management, offering a roadmap for communities, governments and organizations to enhance their preparedness and mitigation strategies. From risk assessment and early warning systems, to community engagement and infrastructure resilience, each chapter provides actionable insights and case studies that illuminate the path towards building robust resilience frameworks. With a keen focus on adaptability and innovation, this book equips readers with the tools necessary to navigate the complexities of today's dynamic world, fostering a culture of preparedness that can mitigate the impact of disasters and safeguard lives and livelihoods.
Keywords: Emergency management.; elektronické knihy; electronic books